1993
DOI: 10.1152/ajpcell.1993.264.1.c209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of ATP conservation during ischemia in slow and fast heart rate hearts

Abstract: In the present study we compared the quantitatively most important, Pi-activated mechanisms for conserving ATP during ischemia in dog and rat cardiac muscle. Earlier studies by ourselves showed that dog heart, like all slow heart rate mammalian hearts examined, possesses the ability to inhibit its mitochondrial ATPase by binding IF1, the ATPase inhibitor protein, during ischemia. Rat heart, like other fast heart rate mammalian hearts studied, does not. The present study demonstrated that this IF1-mediated ATPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Opening mitochondrial K ATP channels results in a dissipation of the inner mitochondrial membrane potential (7), which leads to uncoupling of the oxidative phosphorylation and net oxidation of the mitochondria (7,9,10). Observations have suggested that mitochondrial K ATP channel activation may counteract ATP wastage and preserve cellular functions possibly through activation of endogenous mitochondrial ATPase inhibitor (IF 1 ), or blocking the Ca 2+ uniporter of the mitochondrion or changing the glycolytic pathways during ischemia (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opening mitochondrial K ATP channels results in a dissipation of the inner mitochondrial membrane potential (7), which leads to uncoupling of the oxidative phosphorylation and net oxidation of the mitochondria (7,9,10). Observations have suggested that mitochondrial K ATP channel activation may counteract ATP wastage and preserve cellular functions possibly through activation of endogenous mitochondrial ATPase inhibitor (IF 1 ), or blocking the Ca 2+ uniporter of the mitochondrion or changing the glycolytic pathways during ischemia (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of this phenomenon is not understood, an opening of mitochondrial K + channels seems to be involved that results in dissipation of the inner mitochondrial membrane potential. This leads to net oxidation of the mitochondria with an apparent reduction in energy wastage (7,9,10).Diazoxide is known to act on K ATP channels in the plasma membrane of ␤-cells (11). It hyperpolarizes the membrane and inhibits the energy-consuming process of insulin secretion (12).…”
mentioning
confidence: 99%
“…On the other hand, several groups have shown that preconditioning can be independent of mitochondrial F 1 F 0 -ATPase inhibition [7980]. However, this inhibitor protein is much more active in slow heart rate species such as rabbits and pigs, and has lower activity in mouse and rat heart [8182]. This inhibitor may account for the much slower rate of ATP depletion in slow heart rate species than high heart rate species during ischemia, but since ischemic preconditioning is equally effective in rats, rabbits, and pigs, it is unlikely that this inhibitor is solely responsible for the effect of ischemic preconditioning on ATP consumption.…”
Section: Other Factors In Mitochondrial Adenine Nucleotide Metabolismmentioning
confidence: 99%
“…However, the question regarding how opening the mitochondrial K ATP channel protects the myocyte against ischemic insult still remains unclear. The function of the mitochondrial K ATP channel was shown to include modulation of the mitochondrial volume [18] and energy possibly by inhibiting ATP wastage [19] as opposed to electrical activity for the sarcolemmal K ATP channel [20]. Since the K ATP channel opener-treated hearts have been shown to maintain higher ATP levels and exhibit reduced infarct size and enhanced postischemic recovery upon reperfusion, opening the mitochondrial K ATP channel may be a necessary component in myoprotective mechanisms.…”
Section: Role Of Mitochondrial K Atp Channel In Ipcmentioning
confidence: 99%